Graywater application for landscape irrigation: greenhouse studies - Shogbon, Alicia R., author; Sharvelle, Sybil E., advisor; Shackelford, Charles D., committee member; Qian, Yaling, committee member (Colorado State University. Libraries, 2010)
Over the years, residential graywater application for landscape irrigation has garnered increasing popularity. Concerns however exist regarding the potential negative impacts that graywater pose to plant health and environmental quality. Due to the variability in field conditions such as graywater loading rate, soil type, climate and rainfall amount difficulty exists in accurately determining the potential for groundwater contamination. The need therefore arises to evaluate impacts of graywater irrigation in a controlled environment to develop scientifically justified conclusions regarding the fate of graywater constituents. The objective of this study was to conduct experiments in a greenhouse to evaluate the potential for groundwater contamination by conducting leachate analysis. Plant health was also evaluated throughout the duration of the experiment. The experiment setup involved the use of thirty-eight custom polyvinyl chloride (PVC) pots. These pots were setup in the Colorado State University greenhouse. Potable water served as a control for the experiments. Two different plants and two different turfgrasses were utilized. The turfgrasses were bermudagrass (a warm season grass) and tall fescue (a cool season grass). The landscape plants used were euonymous (a shrub) and lemon (a citrus). The pots were setup to allow for leachate collection from the bottom. The leachate volume was monitored and recorded and leachate analyses were conducted for boron, sodium adsorption ratio (SAR), nitrate, ammonium, total nitrogen (TN), total dissolved solids (TDS), total suspended solids (TSS), volatile suspended solids (VSS), total organic carbon (TOC), sulfate, conductivity and surfactants (linear alkylbenzene sulfonate (LAS), alkyl ethoxy sulfate (AES), and alcohol ethoxylate (AE)). Analysis of the leachate from the graywater irrigated pots revealed on average, elevated levels of TOC, TN, nitrate, ammonium, TDS, TSS, VSS, sulfate, conductivity, boron and SAR when compared to the concentrations measured in the leachate from the control systems. The average concentrations of TOC, TSS, VSS , ammonium, nitrate and TN measured in the leachate from the graywater irrigated plant/grass systems were however lower than the concentrations in the synthetic graywater. An expected increase in conductivity and TDS in the leachate from the graywater irrigated pots was found. Results further indicate the accumulation of boron and salts (indicated by SAR) in the graywater systems with a trend of increasing concentrations with time and a subsequent increase in measured leachate concentrations above the input concentration measured in the graywater. With the exception of boron and salts, there was substantial percentage retention of graywater constituents through the soil column such that there was lower measured concentrations of the graywater constituents in the soil leachate compared to the input concentrations.
Keywords: graywater; leachate; groundwater; Landscape irrigation; Graywater (Domestic wastewater); Plants -- Effect of graywater on; Leachate